Method for laser infiltration of a TiC reinforced submerged arc weld layer and wear-resistant component

CN122918564APending Publication Date: 2026-10-16SUZHOU WEIAODE WELDING MATERIAL & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611419219.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-14
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0008]本发明的目的是要解决重载构件表面耐磨强化与修复中耐磨性、成形质量、尺寸精度与工艺稳定性难以兼顾的问题,获得性能更优且成形和尺寸可控的表面强化层

Benefits of technology

与现有技术相比,本发明通过将 TiC 颗粒的引入工序从埋弧焊阶段转移至氩气保护的激光表面重熔阶段,使 TiC 颗粒完全避开埋弧焊熔剂熔渣反应体系,在保留埋弧堆焊高效沉积优势的同时,避免了直接添加 TiC 所引起的黏渣、脱渣困难和焊道表面不均匀问题。由于激光熔渗仅作用于堆焊层表面薄层、TiC 等效留存质量分数较低,引入的材料总量有限,熔渗层厚度增加和工件整体尺寸变化均很小,热影响区域也较为有限,适于在已接近最终尺寸的构件上进行表面强化而无需预留大量加工余量。激光重熔形成的熔池为 TiC颗粒的进入与保留提供了必要条件,而 TiC 颗粒在凝固过程中通过非均质形核、枝晶钉扎和晶粒长大抑制等作用改变了熔池的凝固行为,使熔渗层组织在激光快速凝固基础上进一步细密化,二者相互配合形成协同强化效果。本发明方法引入的TiC 颗粒在接触表面提供硬质承载点以限制磨粒犁削和材料脱落,同时其对凝固组织的调控作用改善了组织均匀性并减少了粗大连续组织区域,使熔渗层的摩擦系数和磨损率均得到优化,分别有利于降低摩擦过程中的能量损耗与界面温升、延长构件的耐磨服役寿命。该方法对低铬合金钢和马氏体不锈钢两类常用埋弧堆焊层均适用,且在马氏体不锈钢体系中能够抑制单纯激光重熔引起的晶粒长大倾向,保证了组织细化和耐磨提升效果在不同合金体系中的稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122918564A_ABST
    Figure CN122918564A_ABST
Patent Text Reader

Abstract

The present application belongs to the technical field of heavy load construction surface strengthening, and particularly relates to a method for laser infiltrating TiC reinforced submerged arc surfacing layer and a wear-resistant component. The present application prepares a submerged arc surfacing layer on the surface of a steel base. After surface pretreatment, laser scanning is used to form a remelted zone on the surface of the surfacing layer. At the same time, a powder feeding device is used to synchronously feed TiC particles into the remelted zone, so that TiC is left in the infiltrated layer during solidification of the molten pool. The equivalent mass fraction of TiC is controlled at 0.5-3.0 wt.%. The present application separates the introduction of TiC from the submerged arc welding flux slag system, avoiding the sticky slag and poor weld formation caused by direct addition of TiC. TiC has a dual role of hard bearing and solidification structure control in the infiltrated layer, and forms a synergistic strengthening with laser rapid solidification, significantly improving the wear resistance of the infiltrated layer and reducing the friction coefficient. The present application has a small effect on the overall size of the workpiece, and is suitable for various surfacing material systems such as low-chromium alloy steel and martensitic stainless steel.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of heavy-duty construction surface strengthening technology, specifically relating to a method for laser infiltration of TiC to strengthen submerged arc weld overlay and wear-resistant components. Background Technology

[0002] Heavy-duty components such as rolls, roller conveyors, guides, and liners are widely used in industries such as metallurgy, mining, power, and building materials. During service, they endure long-term abrasive wear, reciprocating sliding, and certain impact loads, making surface wear one of their main failure modes. To improve the surface performance of these components, there are two main requirements in actual production: first, surface strengthening during the manufacturing stage of new components, which involves forming a highly wear-resistant working layer on the surface of a steel substrate, requiring good forming quality and adaptability to different welding material systems such as low-chromium alloy steel and martensitic stainless steel; second, repair and remanufacturing of worn old components, which involves restoring dimensions and improving surface performance through surface welding and other methods. In this case, the bonding strength between the repair layer and the substrate, the overall dimensional changes, and the difficulty of subsequent processing are particularly critical. Whether strengthening or repairing, it is desirable for the surface layer to possess high wear resistance, stable forming quality, and good processability. However, the requirements for dimensional accuracy and processing costs are even more stringent in repair scenarios.

[0003] A common approach to improving the wear resistance of weld overlays is to adjust the alloy composition, such as increasing the content of carbide-forming elements like Cr, Mo, V, and W, or controlling the C content to regulate the matrix structure and the quantity, morphology, and distribution of carbides. Theoretically, appropriately increasing the alloy content can increase the number of hard particles and improve matrix hardness, thereby enhancing wear resistance. However, increasing the alloy content is constrained by the material's toughness and weldability: excessively high alloy content leads to increased hardness but decreased toughness, making it prone to cracking or spalling under impact loads; high-alloy materials have increased weld crack sensitivity, requiring stricter control over preheating, interpass temperature, and welding heat input, narrowing the process window. In repair applications, excessively high alloy content also increases post-weld machining difficulty, hindering control of machining allowances and repair costs.

[0004] Another material approach involves directly introducing second-phase hard particles such as carbides and borides into the weld filler material. These high-hardness particles can act as load-bearing elements in the metal matrix and limit abrasive ploughing, theoretically improving wear resistance. However, second-phase particles often differ from molten metal and slag in wettability, density, and thermal stability, affecting slag viscosity and interfacial reactions, which in turn affect slag removal and weld surface formation. Furthermore, particles may dissolve, float, or agglomerate in the molten pool, making their retention rate and distribution uniformity highly sensitive to welding heat input, molten pool flow, and the particle's own characteristics. Therefore, directly introducing second-phase particles in actual welding may face difficulties such as a narrowed process window, unstable surface formation, and uneven particle distribution.

[0005] Besides material adjustments, post-treatment methods such as surface heat treatment, shot peening, laser surface remelting, or thermal spraying can be used after welding to further improve surface properties. Overall quenching and tempering can adjust the microstructure and hardness of the weld overlay, but they consume a lot of energy and are prone to deformation, making them unsuitable for components already machined to near their final dimensions. Mechanical strengthening methods like shot peening have limited depth, and their strengthening effect is greatly affected by the original surface condition, resulting in insufficient repeatability. Laser surface remelting uses a high-energy beam to rapidly melt and solidify the surface of the weld overlay to regulate the microstructure, but the microstructure evolution behavior after remelting is complex and varies greatly among different alloy systems, leading to significant uncertainty in the generation and extent of the strengthening effect. Thermal spraying can prepare ceramic or cermet coatings, but the coating and substrate are mostly mechanically or semi-metallurgically bonded, posing a risk of spalling under heavy impact, and porosity and thickness uniformity are difficult to control.

[0006] In summary, existing technologies often involve material-level adjustments at the expense of process stability, forming quality, or toughness, while post-processing at the process level frequently results in trade-offs between strengthening depth, bonding strength, dimensional impact, or material adaptability. For widely used submerged arc weld overlays of low-chromium alloy steel and martensitic stainless steel, how to further enhance surface wear resistance while simultaneously ensuring forming quality, dimensional accuracy, and process stability remains a pressing technical challenge. Summary of the Invention

[0007] To address the shortcomings of existing technologies, this invention provides a method for laser infiltration of TiC to strengthen submerged arc weld overlay and a wear-resistant component.

[0008] The purpose of this invention is to solve the problem of difficulty in simultaneously achieving wear resistance, forming quality, dimensional accuracy and process stability in the surface wear-resistant strengthening and repair of heavy-duty components, and to obtain a surface strengthening layer with better performance and controllable forming and size.

[0009] The first aspect of this invention provides a method for laser infiltration of TiC to strengthen a submerged arc weld overlay, comprising the following steps: Step 1: Prepare a submerged arc weld overlay on the surface of a steel substrate; Step 2: Under a protective atmosphere, laser scanning is used to form a remelting zone on the surface of the submerged arc weld overlay. At the same time, TiC particles are fed into the remelting zone through a powder feeding device, so that the TiC particles remain in the melt infiltration layer as the molten pool solidifies. The flow rate of TiC particles fed into the melt infiltration layer is controlled by the powder feeding device to ensure that the equivalent mass fraction of TiC in the melt infiltration layer is 0.45 to 3.2 wt.%.

[0010] As a further optimization, the submerged arc weld overlay is a low-chromium alloy steel submerged arc weld overlay.

[0011] As a further optimization, the submerged arc weld overlay is a martensitic stainless steel submerged arc weld overlay.

[0012] As a further optimization, the equivalent mass fraction of TiC retained in the infiltrated layer is 0.5–3.0 wt.%, and more preferably 1.3–1.7 wt.%.

[0013] As a further optimization, the TiC particle size is 53–150 μm; the TiC particles are dry when fed in.

[0014] As a further optimization, the laser scanning process parameters are: laser power 2000–3200 W, scanning speed 8–16 mm / s, a circular spot with a diameter of 3–7 mm, and an overlap rate of 40%–60% between adjacent scanning tracks. More preferably, the laser power is 2700 W, the scanning speed is 12 mm / s, the spot is a circular spot with a diameter of 5 mm, and the overlap rate between adjacent scanning tracks is 50%.

[0015] As a further optimization approach, the TiC equivalent retention quality score is controlled using a closed-loop method, including the following steps: Step A: Prepare a laser infiltration calibration area on the surface of the submerged arc weld overlay layer in the same batch as the formal test sample; Step B: After the calibration area cools down, remove the surface oxide layer and grind the test surface flat. Use a direct-reading spectrometer to perform multi-point detection along the length of the calibration area. Take the average Ti mass fraction of each test point as the Ti detection result and subtract the Ti background value of the un-melted weld overlay. Step C: Based on the relative molecular mass relationship between TiC and Ti, convert the net increase in Ti mass fraction into the equivalent retained TiC mass fraction; Step D: Compare the equivalent retention mass fraction of TiC with the target value and calculate the relative deviation. If the relative deviation is ≤10%, the current powder feeding settings are considered to meet the requirements. If the detected value is lower than the allowable range, increase the powder feeding flow rate. If it is higher than the allowable range, decrease the powder feeding flow rate and re-prepare the calibration area for detection until the relative deviation is ≤10%.

[0016] As a further optimization, the composition of the low-chromium alloy steel submerged arc weld overlay, by mass percentage, is: C 0.20%–0.40%, Cr 4.0%–6.5%, Mn 0.8%–1.2%, Si 0.6%–1.0%, Mo 1.0%–2.0%, W 0.5%–1.5%, V 0.2%–0.6%, with the balance being Fe and unavoidable impurities, and the content of impurities S and P both controlled below 0.03%. More preferably, the composition is C 0.30%, Cr 5.20%, Mn 1.00%, Si 0.80%, Mo 1.50%, W 1.00%, and V 0.40%.

[0017] As a further optimization, the composition of the martensitic stainless steel submerged arc weld overlay, by mass percentage, is: C 0.15%–0.35%, Cr 12%–15%, Mn 0.8%–1.5%, Si 0.5%–0.9%, Ni 1.0%–2.0%, Mo 0.5%–1.5%, with the balance being Fe and unavoidable impurities, and the content of impurities S and P both controlled below 0.03%. More preferably, the composition is C 0.25%, Cr 13.50%, Mn 1.20%, Si 0.70%, Ni 1.50%, and Mo 1.00%.

[0018] As a further optimization, the submerged arc weld overlay is prepared using a submerged arc welding process with the following parameters: welding wire diameter 3.0–5.0 mm, flux basicity 2.0–4.0, welding voltage 28–36 V, welding current 400–550 A, and welding speed 300–500 mm / min. More preferably, the welding wire diameter is 4.0 mm, flux basicity is 3.0, welding voltage is 32 V, welding current is 480 A, and welding speed is 400 mm / min.

[0019] As a further optimization, the protective gas is argon, and the argon flow rate is 8–15 L / min. More preferably, the argon flow rate is 10 L / min.

[0020] As a further optimization, the steel matrix is ​​made of carbon structural steel.

[0021] As a further optimization, it also includes pretreatment of the surface of the submerged arc weld overlay prepared on the steel substrate; the pretreatment includes slag removal, grinding, cleaning and drying of the surface of the submerged arc weld overlay.

[0022] A second aspect of the present invention provides a wear-resistant component, which is manufactured by the above method and includes a steel substrate, a submerged arc weld overlay layer disposed on the surface of the steel substrate, and a TiC particle-reinforced laser infiltration layer located on the surface of the submerged arc weld overlay layer; the equivalent retention mass fraction of TiC in the TiC particle-reinforced laser infiltration layer is 0.5 to 3.0 wt.%; the depth of the TiC particle-reinforced laser infiltration layer is 0.2 to 3.0 mm; the submerged arc weld overlay layer is a low-chromium alloy steel submerged arc weld overlay layer or a martensitic stainless steel submerged arc weld overlay layer.

[0023] Beneficial effects Compared with existing technologies, this invention shifts the TiC particle introduction process from the submerged arc welding stage to the argon-protected laser surface remelting stage. This allows the TiC particles to completely avoid the reaction system of the submerged arc welding flux and slag, retaining the advantages of efficient deposition in submerged arc welding while avoiding the problems of slag adhesion, slag removal difficulties, and uneven weld surface caused by directly adding TiC. Since laser infiltration only acts on a thin layer on the surface of the weld overlay, the equivalent retention mass fraction of TiC is low, the total amount of material introduced is limited, the increase in the thickness of the infiltrated layer and the change in the overall size of the workpiece are minimal, and the heat-affected zone is also relatively limited. This is suitable for surface strengthening on components that are close to their final dimensions without reserving a large amount of machining allowance. The molten pool formed by laser remelting provides the necessary conditions for the entry and retention of TiC particles. During solidification, the TiC particles alter the solidification behavior of the molten pool through heterogeneous nucleation, dendrite pinning, and grain growth inhibition, further refining the microstructure of the infiltrated layer based on rapid laser solidification. The two work together to create a synergistic strengthening effect. The TiC particles introduced in this invention provide hard bearing points on the contact surface to limit abrasive plowing and material shedding. Simultaneously, their regulation of the solidification structure improves microstructure uniformity and reduces regions of coarse, continuous microstructure, thus optimizing the friction coefficient and wear rate of the melt-infiltrated layer. This benefits both reducing energy loss and interface temperature rise during friction and extending the wear-resistant service life of the component. This method is applicable to both low-chromium alloy steel and martensitic stainless steel, two commonly used submerged arc weld overlays. Furthermore, in martensitic stainless steel systems, it can suppress the grain growth tendency caused by simple laser remelting, ensuring the stability of microstructure refinement and wear resistance improvement effects across different alloy systems. Attached Figure Description

[0024] Figure 1 The graph shows the change in the friction coefficient over time for the unremelted layer of low-chromium alloy steel (Comparative Example 1).

[0025] Figure 2 The friction coefficient of low-chromium alloy steel without TiC laser remelting layer (Comparative Example 2) varies with time.

[0026] Figure 3The friction coefficient of a 1.5 wt.% TiC laser infiltration layer made of low-chromium alloy steel (Example 2) varies with time.

[0027] Figure 4 The graph shows the change in the friction coefficient over time for the unremelted layer of martensitic stainless steel (Comparative Example 3).

[0028] Figure 5 shows the friction coefficient of the TiC-free laser remelted layer of martensitic stainless steel (Comparative Example 4) as a function of time.

[0029] Figure 6 The graph shows the change in friction coefficient over time for a 1.5 wt.% TiC laser-infiltrated layer of martensitic stainless steel (Example 5).

[0030] Figure 7 The image shows the microstructure of the unremelted layer of low-chromium alloy steel (Comparative Example 1).

[0031] Figure 8 Microstructure of TiC-free laser remelted layer of low-chromium alloy steel (Comparative Example 2).

[0032] Figure 9 Microstructure of a 1.5 wt.% TiC laser infiltration layer in low-chromium alloy steel (Example 2).

[0033] Figure 10 The image shows the microstructure of the unremelted layer of martensitic stainless steel (Comparative Example 3).

[0034] Figure 11 Microstructure of TiC-free laser remelted layer of martensitic stainless steel (Comparative Example 4).

[0035] Figure 12 Microstructure of a 1.5 wt.% TiC laser infiltration layer in martensitic stainless steel (Example 5).

[0036] Figure 13 Metallographic image of a cross section of a 1.5 wt.% TiC laser infiltration layer on low-chromium alloy steel (Example 2).

[0037] Figure 14 A photograph of the weld surface after directly adding 0.5 wt.% TiC (Comparative Example 5) to the filler material for submerged arc welding of low-chromium alloy steel.

[0038] Figure 15 A photograph of the weld surface after directly adding 1.0 wt.% TiC (Comparative Example 6) to the filler material for submerged arc welding of low-chromium alloy steel. Detailed Implementation

[0039] The present invention is further illustrated below with specific embodiments. These embodiments are exemplary and intended to illustrate the problem and explain the present invention, and are not intended to be limiting.

[0040] All the laser infiltration examples below were performed on submerged arc weld overlays already prepared on the surface of Q235 steel substrates, and TiC laser infiltration was not performed directly on bare steel substrates. The actual main components of the submerged arc weld overlays used in the low-chromium alloy steel series and the martensitic stainless steel series are shown in Table 1 and Table 2, respectively, and the S and P contents of both types of weld overlays are controlled below 0.03%.

[0041] Table 1. Actual main components of the main test steel substrate and submerged arc weld overlay.

[0042] Table 2. Other components and submerged arc welding parameters of the main test submerged arc weld overlay.

[0043] All laser infiltration examples used the same batch of TiC powder, with a sieve particle size of 100–270 mesh, corresponding to a particle size of 53–150 μm. The TiC powder was dried before being fed into the laser and loaded into an independent powder feeding device. The laser power was 2700 W, the scanning speed was 12 mm / s, the spot size was a 5 mm circular spot, the overlap rate between adjacent scanning tracks was 50%, the protective gas was argon, the argon flow rate was 10 L / min, and the infiltration layer depth was controlled between 0.2 and 3.0 mm.

[0044] In the following laser melting infiltration embodiments, the control method for the equivalent retention mass fraction of TiC is as follows: the three target contents of 0.5 wt.%, 1.5 wt.%, and 3.0 wt.% are not directly determined by the nominal amount fed by the powder feeder, but are controlled in a closed-loop manner. The specific steps are as follows.

[0045] Step 1: Based on previous laser melting and infiltration test experience and powder feeder calibration curve, select three initial powder feeding settings (low, medium, and high) for three target contents: 0.5 wt.%, 1.5 wt.%, and 3.0 wt.%. Except for the powder feeding flow rate, the laser power, scanning speed, spot size, overlap rate, and argon flow rate remain unchanged.

[0046] Step 2: Prepare a laser infiltration calibration area with a width of 10 mm and a length of 100 mm on the surface of the submerged arc weld overlay layer, identical to that of the formal sample. After the calibration area cools, remove the surface oxide layer and grind the test surface smooth.

[0047] Step 3: Use a direct-reading spectrometer to perform multi-point detection along the length of the calibration area, and take the average Ti mass fraction of each detection point as the Ti detection result for the calibration area. To eliminate the influence of trace Ti in the original weld overlay, first detect the Ti background value of the un-infiltrated weld overlay and subtract it.

[0048] Step 4: Based on the relative molecular mass relationship between TiC and Ti, convert the net increase in Ti mass fraction into an equivalent TiC retention mass fraction: w(TiC,eq)=1.251×[w(Ti, melt penetration layer)-w(Ti, original weld overlay layer)]. This result is used to represent the equivalent retention contributed by the synchronously fed TiC and is not used to distinguish TiC particles, dissolved Ti, or other Ti-containing phases.

[0049] Step 5: The relative deviation between the equivalent TiC retention mass fraction and the target value is calculated as δ = |w(TiC,eq) - w(target)| / w(target) × 100%. If δ ≤ 10%, the powder feeding settings are considered to meet the requirements. If the detected value is lower than the allowable range, the powder feeding flow rate is increased; if it is higher than the allowable range, the powder feeding flow rate is decreased, and a new 10 mm × 100 mm calibration area is prepared for testing until it enters the allowable range.

[0050] Table 3. Permissible range of TiC equivalent retention mass fraction

[0051] Example 1 (L1, low-chromium alloy steel, 0.5 wt.% TiC) Low-chromium alloy steel submerged arc weld overlays (SAW) as listed in Tables 1 and 2 were prepared on the surface of a Q235 steel substrate. The SAW layers were then cleaned, ground, washed with anhydrous ethanol, and dried. An initial powder feed rate was set, and a 10 mm × 100 mm laser infiltration calibration area was formed on the surface of the same batch of SAW layers. Ti was detected using a direct-reading spectrometer, and the equivalent TiC retention mass fraction was calculated. Feedback correction was performed by increasing or decreasing the powder feed rate until the detection result entered the range of 0.45–0.55 wt.%. Subsequently, using the corrected powder feed settings, a remelting zone was formed on the surface of the SAW layer by laser scanning under argon protection. Simultaneously, TiC particles were fed into the remelting zone through an independent powder feed device to prepare the L1 formal sample. The target equivalent TiC retention mass fraction of this sample was 0.5 wt.%, and the corrected actual equivalent TiC retention mass fraction was 0.51 wt.%.

[0052] Example 2 (L2, low-chromium alloy steel, 1.5 wt.% TiC) Low-chromium alloy steel submerged arc weld overlays (SAW) as listed in Tables 1 and 2 were prepared on the surface of a Q235 steel substrate. The SAW layers were then cleaned, ground, washed with anhydrous ethanol, and dried. An initial powder feed rate was set, and a 10 mm × 100 mm laser infiltration calibration area was formed on the surface of the same batch of SAW layers. Ti was detected using a direct-reading spectrometer, and the equivalent TiC retention mass fraction was calculated. Feedback correction was performed by increasing or decreasing the powder feed rate until the detection result fell within the range of 1.35–1.65 wt.%. Subsequently, using the corrected powder feed settings, a remelting zone was formed on the surface of the SAW layer by laser scanning under argon protection. Simultaneously, TiC particles were fed into the remelting zone through an independent powder feed device to prepare the L2 formal sample. The target equivalent TiC retention mass fraction of this sample was 1.5 wt.%, and the corrected actual equivalent TiC retention mass fraction was 1.48 wt.%.

[0053] Example 3 (L3, low-chromium alloy steel, 3.0 wt.% TiC) Low-chromium alloy steel submerged arc weld overlays (SAW) as listed in Tables 1 and 2 were prepared on the surface of a Q235 steel substrate. The SAW layers were then cleaned, ground, washed with anhydrous ethanol, and dried. An initial powder feed rate was set, and a 10 mm × 100 mm laser infiltration calibration area was formed on the surface of the same batch of SAW layers. Ti was detected using a direct-reading spectrometer, and the equivalent TiC retention mass fraction was calculated. Feedback correction was performed by increasing or decreasing the powder feed rate until the detection result fell within the range of 2.70–3.30 wt.%. Subsequently, using the corrected powder feed settings, a remelting zone was formed on the surface of the SAW layer by laser scanning under argon protection. Simultaneously, TiC particles were fed into the remelting zone through an independent powder feeder to prepare the L3 formal sample. The target equivalent TiC retention mass fraction of this sample was 3.0 wt.%, and the corrected actual equivalent TiC retention mass fraction was 2.89 wt.%.

[0054] Example 4 (M1, martensitic stainless steel, 0.5 wt.% TiC) Martensitic stainless steel submerged arc weld overlays (SAW) as listed in Tables 1 and 2 were prepared on the surface of a Q235 steel substrate. The SAW layers were then cleaned, ground, washed with anhydrous ethanol, and dried. An initial powder feed rate was set, and a 10 mm × 100 mm laser infiltration calibration area was formed on the surface of the same batch of SAW layers. Ti was detected using a direct-reading spectrometer, and the equivalent TiC retention mass fraction was calculated. Feedback correction was performed by increasing or decreasing the powder feed rate until the detection result entered the range of 0.45–0.55 wt.%. Subsequently, using the corrected powder feed settings, a remelting zone was formed on the surface of the SAW layer by laser scanning under argon protection. Simultaneously, TiC particles were fed into the remelting zone through an independent powder feeder to prepare the M1 formal sample. The target equivalent TiC retention mass fraction of this sample was 0.5 wt.%, and the corrected actual equivalent TiC retention mass fraction was 0.49 wt.%.

[0055] Example 5 (M2, martensitic stainless steel, 1.5 wt.% TiC) Martensitic stainless steel submerged arc weld overlays (SAWs) as listed in Tables 1 and 2 were prepared on the surface of a Q235 steel substrate. The SAWs were then cleaned, ground, washed with anhydrous ethanol, and dried. An initial powder feed rate was set, and a 10 mm × 100 mm laser infiltration calibration area was formed on the surface of the same batch of SAWs. Ti was detected using a direct-reading spectrometer, and the equivalent TiC retention mass fraction was calculated. Feedback correction was performed by increasing or decreasing the powder feed rate until the detection result fell within the range of 1.35–1.65 wt.%. Subsequently, using the corrected powder feed settings, a remelting zone was formed on the surface of the SAW under argon protection using laser scanning. Simultaneously, TiC particles were fed into the remelting zone through an independent powder feeder to prepare the M2 formal sample. The target equivalent TiC retention mass fraction of this sample was 1.5 wt.%, and the corrected actual equivalent TiC retention mass fraction was 1.51 wt.%.

[0056] Example 6 (M3, martensitic stainless steel, 3.0 wt.% TiC) Martensitic stainless steel submerged arc weld overlays (SAWs) as listed in Tables 1 and 2 were prepared on the surface of a Q235 steel substrate. The SAWs were then cleaned, ground, washed with anhydrous ethanol, and dried. An initial powder feed rate was set, and a 10 mm × 100 mm laser infiltration calibration area was formed on the surface of the same batch of SAWs. Ti was detected using a direct-reading spectrometer, and the equivalent TiC retention mass fraction was calculated. Feedback correction was performed by increasing or decreasing the powder feed rate until the detection result fell within the range of 2.70–3.30 wt.%. Subsequently, using the corrected powder feed settings, a remelting zone was formed on the surface of the SAW under argon protection using laser scanning. Simultaneously, TiC particles were fed into the remelting zone through an independent powder feeder to prepare the M3 formal sample. The target equivalent TiC retention mass fraction of this sample was 3.0 wt.%, and the corrected actual equivalent TiC retention mass fraction was 3.10 wt.%.

[0057] Comparative Example 1 (L0, original unremelted layer of low-chromium alloy steel) Test plates with a low-chromium alloy steel submerged arc weld overlay, from the same batch as those used in Examples 1-3, were used. After welding, only slag removal, grinding, cleaning, and drying were performed; laser remelting was not performed, and TiC particles were not introduced. Subsequently, SEM observation samples and reciprocating friction and wear samples were prepared using the same sampling and sample preparation methods as in the examples.

[0058] Comparative Example 2 (LR, low-chromium alloy steel without TiC laser remelting layer) Test plates with low-chromium alloy steel submerged arc weld overlays, from the same batch as those in Examples 1-3, were used. The laser parameters were consistent with those in Examples 1-3, and the TiC powder feeding device was in the off state. After slag removal, grinding, cleaning, and drying of the weld overlay, surface remelting was performed using the aforementioned laser parameters.

[0059] Comparative Example 3 (M0, original unremelted layer of martensitic stainless steel) Test plates with martensitic stainless steel submerged arc weld overlays, from the same batch as those used in Examples 4-6, were used. After welding, only slag removal, grinding, cleaning, and drying were performed; laser remelting was not performed, and TiC particles were not introduced. Subsequently, SEM observation samples and reciprocating friction and wear samples were prepared using the same sampling and sample preparation methods as in the examples.

[0060] Comparative Example 4 (MR, martensitic stainless steel without TiC laser remelting layer) Test plates with martensitic stainless steel submerged arc weld overlays, from the same batch as those in Examples 4-6, were used. The laser parameters were consistent with those in Examples 4-6, and the TiC powder feeding device was turned off. After slag removal, grinding, cleaning, and drying of the weld overlay, surface remelting was performed using the aforementioned laser parameters.

[0061] Comparative Example 5 (0.5 wt.% TiC directly added to low-chromium alloy steel submerged arc welding material) The base material is Q235 steel. The design composition of the filler material for submerged arc welding of low-chromium alloy steel is C 0.40%, Cr 6.20%, Mn 1.20%, Si 0.70%, Mo 1.00%, W 1.00%, TiC 0.50%, with the balance being Fe and unavoidable impurities. The TiC particle size is 53–150 μm. A 4.0 mm diameter submerged arc welding wire is used, with a flux basicity of 3.0, a welding voltage of 32 V, a welding current of 480 A, and a welding speed of 400 mm / min.

[0062] TiC particles were directly mixed into the low-chromium alloy steel submerged arc welding filler material according to the above ratio. After uniform mixing, submerged arc welding was performed. After welding, the material was allowed to cool naturally, and the surface flux and slag were removed. The slag removal performance and the surface formation of the weld bead after slag removal were observed and recorded.

[0063] Comparative Example 6 (1.0 wt.% TiC directly added to low-chromium alloy steel submerged arc welding material) Except for the TiC content, the matrix materials, basic alloy composition, TiC particle size, welding wire specifications, flux basicity, and submerged arc welding process parameters were all the same as those in Comparative Example 5. The only difference was that the TiC content was increased from 0.50% to 1.00%, with the balance still being Fe and unavoidable impurities. The experiment was conducted using the same batching and submerged arc welding steps as in Comparative Example 5. After welding, the material was allowed to cool naturally, and the surface flux and slag were removed. The slag removal performance and the surface formation of the weld bead after slag removal were observed and recorded.

[0064] Test methods Cross-sectional metallographic observation involves cutting a section of the laser-infiltrated sample perpendicular to the scanning direction, then mounting, grinding, and polishing it before using a metallographic microscope to observe the cross-sectional morphology of the infiltrated layer, measuring the infiltration depth, and observing the surface contour forming quality.

[0065] Scanning electron microscopy (SEM) observation involves observing tissues after the sample has been ground, polished, and etched. All images are taken at a uniform magnification of 500x and a scale bar of 20 μm, and are displayed under the same imaging conditions.

[0066] Reciprocating friction and wear tests were conducted using a reciprocating friction and wear testing machine. Before the test, the sample surface was ground and polished, then cleaned and dried with anhydrous ethanol. The wear pair consisted of Si3N4 ceramic balls with a diameter of 6 mm. The normal load was 20 N, the reciprocating frequency was 2 Hz, the reciprocating stroke was 5 mm, and the test time was 30 min. The friction coefficient was continuously recorded during the test. After the test, the cross-sectional profile of the wear track was measured. The wear volume V was calculated based on the cross-sectional area and length of the wear track, and the wear rate was calculated using K=V / (F·L), where F is the normal load and L is the total sliding distance. (The text repeats itself here.)

[0067] Experimental Results and Analysis The results of the reciprocating friction and wear tests are shown in Tables 4 and 5. In the low-chromium alloy steel series, the wear rates of the samples in Examples 1 to 3 were significantly improved compared to Comparative Examples 1 and 2. Specifically, Example 2 showed a 20.74% reduction compared to Comparative Example 1 and a 10.27% reduction compared to Comparative Example 2. The martensitic stainless steel series exhibited the same trend: the wear rates of the samples in Examples 4 to 6 were significantly improved compared to Comparative Examples 3 and 4. Specifically, Example 5 showed a 16.79% reduction compared to Comparative Example 3 and a 10.35% reduction compared to Comparative Example 4.

[0068] Table 4. Friction and Wear Results of Low-Chromium Alloy Steel Series

[0069] Table 5. Friction and Wear Results of Martensitic Stainless Steel Series

[0070] The friction coefficients versus time curves for Comparative Example 1, Comparative Example 2, and Example 2 in the low-chromium alloy steel series samples are shown below. Figure 1 , Figure 2 and Figure 3As shown. The friction coefficient of Comparative Example 1 stabilized in the range of 0.59–0.63 after the running-in stage; the friction coefficient of Comparative Example 2 stabilized in the range of 0.67–0.70 after laser remelting, but its wear rate was lower than that of Comparative Example 1, indicating that the increase in friction coefficient is related to the change in the contact interface state after the microstructure is refined, and does not mean that the wear resistance is reduced; the stable friction coefficient of Example 2 dropped back to 0.56–0.60, and the wear rate was the lowest, indicating that after introducing TiC particles using the method of the present invention, two aspects of optimization are obtained at the same time: on the one hand, the surface state is optimized to reduce the friction coefficient, which is beneficial to reducing energy loss and contact interface temperature rise during the friction process; on the other hand, it promotes a further reduction in wear rate, resulting in less material removal and extended wear life of components.

[0071] The friction coefficient curves of Comparative Example 3, Comparative Example 4, and Example 5 in the martensitic stainless steel series samples are shown below. Figure 4 , Figure 5 and Figure 6 As shown. The stable friction coefficient of Comparative Example 3 was 0.61–0.64; that of Comparative Example 4 increased to 0.72–0.76; and that of Example 5 decreased to 0.66–0.70. The friction coefficient variation trend of the martensitic stainless steel series is similar to that of low-chromium alloy steel, also showing a pattern of lower coefficient in the unremelted layer, higher coefficient in the absence of TiC remelted layer, and lower coefficient in the TiC laser-infiltrated layer. However, the stable friction coefficient of the TiC laser-infiltrated layer is still slightly higher than that of the unremelted layer. In terms of wear rate, the wear of the TiC laser-infiltrated layer is lower than that of the unremelted layer and the TiC remelted layer. The above results once again verify that wear resistance is not solely determined by the friction coefficient, and that the solution of the present invention can effectively reduce wear and thus extend the wear life of components.

[0072] The microstructure morphology images of Comparative Example 1, Comparative Example 2, and Example 2 in the low-chromium alloy steel series samples are shown below. Figure 7 , Figure 8 and Figure 9 As shown. Comparative Example 1 has a relatively coarse texture with obvious regional differences; Comparative Example 2 has improved texture uniformity after rapid solidification; In Example 2, an increase in fine network, short branch, and granular textures is observed, the characteristic spacing is reduced, the area of ​​coarse continuous texture is reduced, and the distribution of granules or fine textures is more coordinated with the matrix continuity.

[0073] The microstructure morphology of Comparative Example 3, Comparative Example 4, and Example 5 in the martensitic stainless steel series samples are shown in Figures 10, 11, and 12, respectively. Compared with the low-chromium alloy steel series, the microstructure variation law of the martensitic stainless steel series samples has its own unique characteristics. Comparative Example 3 has a needle-like or lath-like structure. After remelting, the original structure of Comparative Example 4 was reconstructed, but large polygonal grains can be seen in the figure, and the grain boundary outlines are clearly distinguishable. The grain size is significantly larger than that of the original layer and the TiC infiltrated layer. Moreover, large equiaxed grain regions coexist with locally residual lath-like structures, and the microstructure uniformity is poor. This indicates that in the martensitic stainless steel system, although simple laser remelting remelts and solidifies the original structure, it does not obtain a sufficiently refined structure under the cooling conditions. Instead, a certain degree of grain growth tendency appears. In Example 5, the large-sized polygonal grains and clear grain boundaries shown in Comparative Example 4 were not present. Instead, a large number of fine network and short rod-shaped units were observed. The large-sized continuous lath regions were significantly reduced, the distribution of short rod-shaped and lath structures was more uniform, and the coarse elongated structures disappeared. The overall structural feature scale was significantly smaller than that of Comparative Example 4. This indicates that the method of the present invention, which introduces TiC particles into the surface of martensitic stainless steel by laser melting, not only exhibits wear resistance but also inhibits grain growth, resulting in a better match between the density of the microstructure and the continuity of the matrix.

[0074] The above comparison shows that the method of this invention, which introduces TiC particles, has the dual function of being a hard load-bearing phase and a solidification structure regulating phase. In low-chromium alloy steel, this manifests as further refinement based on remelting refinement; in martensitic stainless steel, it precisely compensates for and improves the unfavorable microstructure changes caused by simple remelting and further achieves microstructure refinement. Combining SEM and wear rate results, the improvement in wear resistance stems from the microstructure reconstruction caused by rapid laser solidification, the contact load-bearing effect of TiC particles, and their synergistic effect on limiting ploughing and material shedding. Furthermore, the method of this invention, which introduces TiC to regulate the solidification structure, is the key factor for achieving stable wear resistance improvement in both types of materials.

[0075] Metallographic observation of the cross-section of the laser infiltration sample from Example 2 was performed, and the results are as follows: Figure 13As shown in the figure, the measured penetration depths at the two locations are 1858.21 μm and 2011.75 μm, respectively, with an average penetration depth of approximately 1934.98 μm (about 1.94 mm). This indicates that a penetration layer depth on the order of approximately 2 mm can be stably obtained under the scheme and process conditions of Example 2. Simultaneously, it can be seen that the overall surface contour after penetration is relatively smooth, without obvious collapse or severe undulations, indicating that the method of the present invention can maintain good surface forming quality while achieving a certain penetration depth. Furthermore, since laser penetration only acts on a thin layer on the surface of the weld overlay, the total amount of material introduced is small, and the thickness increase of the weld overlay layer due to particle introduction is minimal. At the same time, the laser heat input is concentrated, the heat-affected zone is limited, and the changes in the overall size and shape accuracy of the workpiece are minimal. For weld overlay components that have been processed to near or equal to the final size, surface wear resistance strengthening can be achieved without significantly increasing subsequent processing allowances or even without subsequent processing.

[0076] Figure 14 and Figure 15 The images show actual weld surfaces after directly adding 0.5 wt.% (Comparative Example 5) and 1.0 wt.% TiC (Comparative Example 6) to the filler material for submerged arc welding of low-chromium alloy steel, respectively. It is evident that Comparative Example 5 exhibits significant slag adhesion on the weld surface, with the slag tightly bonded to the weld surface, making slag removal difficult. Comparative Example 6 also shows significant slag adhesion, difficulty in slag removal, and uneven weld surface. Even after subsequent slag removal treatment, both weld surfaces exhibited unevenness and localized inhomogeneity. These results indicate that even a low dose of 0.5 wt.% TiC directly participating in the flux-slag reaction in submerged arc welding can significantly negatively impact slag removal and weld surface formation. Therefore, while directly adding TiC to the submerged arc welding filler material is theoretically a reasonable way to introduce the TiC hard phase, in practice, this method struggles to simultaneously achieve particle introduction, stable slag removal, and uniform surface formation, failing to meet practical application requirements.

[0077] In summary, this invention proposes a surface strengthening method for TiC infiltration by submerged arc welding combined with laser-driven powder feeding. After preparing submerged arc weld layers of low-chromium alloy steel and martensitic stainless steel on a Q235 steel substrate, the equivalent mass fraction of TiC on the surface is controlled within the range of 0.5–3.0 wt.% through calibration and adjustment, resulting in a TiC particle-reinforced laser infiltration layer with a depth of 0.2–3.0 mm and a well-formed surface.

[0078] The beneficial effects of this method include: First, it completely separates the introduction of TiC particles from the submerged arc welding flux slag system, avoiding the problems of slag adhesion, difficulty in slag removal, and uneven weld surface caused by direct addition of TiC, thus preserving both the high-efficiency deposition advantages of submerged arc welding and the wear-resistant strengthening effect of TiC particles; Second, the TiC particles introduced by this method have the dual role of a hard load-bearing phase and a solidification structure regulating phase in the melt infiltration layer, forming synergistic strengthening with rapid laser solidification. The wear rate of low-chromium alloy steel and martensitic stainless steel is reduced by 20.74% and 16.79% respectively compared with the original unremelted layer, while the decrease in friction coefficient helps to reduce friction energy consumption and interface temperature rise; Third, although the mechanism of action is different, this method has been found to be applicable to two commonly used welding materials, and in the martensitic stainless steel system, it can also suppress the grain growth tendency caused by simple laser remelting.

[0079] Furthermore, during the implementation of this invention, it was discovered that the friction coefficient may increase after laser remelting, but the wear rate may decrease, indicating that the relationship between the friction coefficient and the wear rate is not simple and monotonic. Therefore, the wear rate should be the primary criterion for evaluating the wear resistance of the laser-infiltrated layer. The contribution of the TiC particles introduced by the method of this invention to wear resistance lies not only in the hard bearing capacity of the contact surface, but also in the intervention in the solidification process of the molten pool, including heterogeneous nucleation, dendrite pinning, and grain growth inhibition. By using a calibration region combined with direct-reading spectral detection and powder flow rate feedback correction, a clear content criterion can be provided for the repeatable implementation of the TiC laser infiltration process.

[0080] The above embodiments are exemplary and are intended to illustrate the technical concept and features of the present invention, so that those skilled in the art can understand the content of the present invention and implement it accordingly. They should not be construed as limiting the scope of protection of the present invention. All equivalent changes or modifications made according to the spirit and essence of the present invention should be covered within the scope of protection of the present invention.

Claims

1. A method for laser infiltration of TiC to strengthen submerged arc weld overlay, characterized in that, Includes the following steps: Step 1: Prepare a submerged arc weld overlay on the surface of a steel substrate; Step 2: Under a protective atmosphere, laser scanning is used to form a remelting zone on the surface of the submerged arc weld overlay. At the same time, TiC particles are fed into the remelting zone through a powder feeding device, so that the TiC particles remain in the melt infiltration layer as the molten pool solidifies. The flow rate of TiC particles fed into the melt infiltration layer is controlled to ensure that the equivalent mass fraction of TiC in the melt infiltration layer is 0.45 to 3.2 wt.%.

2. The method according to claim 1, characterized in that, The submerged arc weld overlay is a low-chromium alloy steel submerged arc weld overlay.

3. The method according to claim 1, characterized in that, The submerged arc weld overlay is a martensitic stainless steel submerged arc weld overlay.

4. The method according to claim 1, characterized in that, The equivalent mass fraction of TiC retained in the infiltrated layer is 0.5–3.0 wt.%; the particle size of the TiC particles is 53–150 μm; and the TiC particles are dry TiC particles when fed in.

5. The method according to claim 1, characterized in that, The laser scanning process parameters are as follows: laser power 2000-3200 W, scanning speed 8-16 mm / s, the spot is a circular spot with a diameter of 3-7 mm, and the overlap rate of adjacent scanning tracks is 40%-60%.

6. The method according to claim 1, characterized in that, The TiC equivalent retention quality fraction is controlled in a closed-loop manner, including the following steps: Step A: Prepare a laser infiltration calibration area on the surface of the submerged arc weld overlay layer in the same batch as the formal test sample; Step B: After the calibration area cools down, remove the surface oxide layer and grind the test surface flat. Use a direct-reading spectrometer to perform multi-point detection along the length of the calibration area. Take the average Ti mass fraction of each test point as the Ti detection result and subtract the Ti background value of the un-melted weld overlay. Step C: Based on the relative molecular mass relationship between TiC and Ti, convert the net increase in Ti mass fraction into an equivalent TiC retained mass fraction; Step D: Compare the equivalent retention mass fraction of TiC with the target value and calculate the relative deviation. If the relative deviation is ≤10%, the current powder feeding settings are considered to meet the requirements. If the detected value is lower than the allowable range, increase the powder feeding flow rate. If it is higher than the allowable range, decrease the powder feeding flow rate and re-prepare the calibration area for detection until the relative deviation is ≤10%.

7. The method according to claim 2, characterized in that, The composition of the low-chromium alloy steel submerged arc weld overlay, by mass percentage, is: C 0.20%–0.40%, Cr 4.0%–6.5%, Mn 0.8%–1.2%, Si 0.6%–1.0%, Mo 1.0%–2.0%, W 0.5%–1.5%, V 0.2%–0.6%, with the balance being Fe and unavoidable impurities, and the content of impurities S and P is controlled below 0.03%.

8. The method according to claim 3, characterized in that, The composition of the martensitic stainless steel submerged arc weld overlay layer, by mass percentage, is: C 0.15%~0.35%, Cr 12%~15%, Mn 0.8%~1.5%, Si 0.5%~0.9%, Ni 1.0%~2.0%, Mo 0.5%~1.5%, with the balance being Fe and unavoidable impurities, and the content of impurities S and P is controlled below 0.03%.

9. The method according to claim 1, characterized in that, The submerged arc weld overlay is prepared using a submerged arc welding process with the following parameters: welding wire diameter 3.0–5.0 mm, flux basicity 2.0–4.0, welding voltage 28–36 V, welding current 400–550 A, and welding speed 300–500 mm / min.

10. A wear-resistant component, characterized in that, The method described in any one of claims 1-9 is used to prepare the material, which includes a steel substrate, a submerged arc weld overlay layer disposed on the surface of the steel substrate, and a TiC particle-reinforced laser infiltration layer located on the surface of the submerged arc weld overlay layer; the equivalent retention mass fraction of TiC in the TiC particle-reinforced laser infiltration layer is 0.5-3.0 wt.%; the depth of the TiC particle-reinforced laser infiltration layer is 0.2-3.0 mm; and the submerged arc weld overlay layer is a low-chromium alloy steel submerged arc weld overlay layer or a martensitic stainless steel submerged arc weld overlay layer.